Molecular structure from a single NMR supersequence - Kupce, E; Claridge, T (Royal Society of Chemistry, 2018)
A new NOAH supersequence (NMR by Ordered Acquisition using 1H-detection) is introduced that allows fast structure elucidation of organic molecules from a single measurement. The application of the proposed NOAH-3 BSC experiment, which combines two new modules (ZZ-HMBC (B) and ASAP-COSY (C)) with multiplicityedited HSQC (S), is exemplified here through its use in computerassisted structure elucidation.